Design and Build Underwater Robot Control System Based on PID (Proportional Integral Derivative)) - Rista .; Elvan Yuniarti; Dewi Lestari (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2021)
Indonesia has wide waters and in it there is very abundant fishery potential such as various species of freshwater and other aquatic biota. The large role of Indonesian waters certainly needs to be supported by a monitoring system that is able to control and monitor conditions underwater, like underwater robot. In this research, the design of an underwater robot based on PID (Proportional Integral Derivative). Robot stability is controlled using PID with feedback from IMU MPU6050 for tilt angle control and feedback from MS5803 pressure sensor for depth position control. This underwater robot is requipped with six DC motors, four DC motors are used to drive the robot in a horizontal direction (forward, backward and turn). In addition, the robot is also equipped with two lamps for lighting the robot. In this research, the underwater robot can maintain stability when given PID parameter values are 0.001 for Kproll, 0.001 for Kiroll, 1 for Kdroll, 0.001 for Kppitch, 0.001 for Kipitch, 1 for Kdpitch, 5 for Kpdepth, 1 for Kidepth and 1 Kddepth.